Nanoengineered biomaterials for spinal cord regeneration - Silva, Rita Catarina Assunção Ribeiro (2019)
[Excerpt] Introduction Spinal cord injuries (SCIs) affect millions of people worldwide, and unfortunately there is no cure. Today most clinical strategies used for SCI treatment are based mainly on the delivery of drugs aimed at controlling the immune response, excitotoxicity, and cell death triggered after an injury so that further damage can be avoided.[...]